Ganoderma Root Rot Incidence in an Afforested Stand of Khair (Acacia catechu Willd.) in Lower Siwaliks of Himachal Pradesh - Kumar, Ashok; Kumar, Surinder; Singh, Ranjeet; Kumar, Shailendra (Indian Forester, 2006)
Acacia catechu is a very important and preferred tree species in afforestation programmes in the lower sub-tropical zone of Himachal Pradesh. It is valued for its heartwood, which is used for extracting katha and cutch, ingredients of a number of Ayurvedic and Unani medicines. It suffers serious disease problem in the form of root rot by Ganoderma lucidum causing great economic losses. Present paper discusses incidence of Ganoderma root rot disease in a khair plantation in lower Siwaliks of Himachal Pradesh. 4.45 per cent tree mortality was recorded which indicated towards an alarming situation. The trees are showing early symptoms of discoloured foliage, trees with stag horn branches and gaps in lines due to removal of dead trees. The inoculum builds up very fast in the area where the sporophores were seen on dead trees, stumps and wood chips in the infected area. Incidence of drying and wilting was more severe in the cultivated portion than the unmanaged part of the land.